Pengaruh Pemberian Pupuk Organik dan Anorganik terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza Sativa L.) di Lahan Sawah Irigasi - Ikhlas Hamzani (Jurnal Pertanian Khairun, 2026)
This study aims to determine the effect of organic fertilizer (straw compost) and inorganic fertilizer (NPK) on the growth and yield of rice plants (Oryza sativa L.) in irrigated rice fields. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Syiah Kuala University, Gayo Lues. This study lasted for five months, from July to November 2025, covering one full planting season. The method used was a factorial Randomized Block Design (RAK) with two treatment factors, namely the dose of organic fertilizer (0, 5, and 10 tons/ha) and the dose of NPK fertilizer (0, 150, and 300 kg/ha), each with three replications. The parameters observed included plant height, number of productive tillers, panicle length, grain weight per hill, and harvest yield (tons/ha). The results showed that the combination of 10 tons/ha of organic fertilizer with 300 kg/ha of NPK produced the highest dry grain yield of 7.82 tons/ha, significantly different (P < 0.05) compared to the control (4.21 tons/ha). The interaction between the two factors significantly affected all growth and yield parameters. The conclusion of this study is that the optimal application of a combination of organic and inorganic fertilizers can increase rice productivity sustainably.